2016
DOI: 10.1086/685715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bosentan on Peripheral Endothelial Function in Patients with Pulmonary Arterial Hypertension or Chronic Thromboembolic Pulmonary Hypertension

Abstract: Endothelin receptor antagonists (ERAs) have been shown to improve the prognosis of patients with pulmonary arterial hypertension (PAH). However, the effect of the oral dual ERA bosentan on peripheral endothelial dysfunction (PED), as assessed by flow-mediated vasodilation (FMD), in patients with pulmonary hypertension is not well characterized. We investigated the effect of bosentan on PED in patients with PAH or inoperable chronic thromboembolic pulmonary hypertension (CTEPH). A total of 18 patients with PAH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Endothelin receptor antagonists (ERAs) are an established therapy for PAH (16,32), but conflicting results of ERA therapy have been reported in patients with CTEPH (24,25,44). The 40% higher plasma ET-1 in our porcine model is slightly less than the doubling observed in patient studies.…”
Section: Discussionmentioning
confidence: 53%
“…Endothelin receptor antagonists (ERAs) are an established therapy for PAH (16,32), but conflicting results of ERA therapy have been reported in patients with CTEPH (24,25,44). The 40% higher plasma ET-1 in our porcine model is slightly less than the doubling observed in patient studies.…”
Section: Discussionmentioning
confidence: 53%
“… 13 In another study, bosentan increased flow mediated vasodilation in PAH. 14 Our data suggest that if ET-1 blockade increases skeletal muscle blood flow at peak exercise in PAH, it does so indiscriminately, without preferential perfusion of the slow-twitch oxidative muscle fiber. Furthermore, the lowered SVR after treatment with ambrisentan suggests that inappropriate systemic vasodilation secondary to the drug might have adversely affected muscle oxygen uptake and utilization.…”
mentioning
confidence: 62%
“…Following three months of bosentan medication, it was shown that FMD increased in PAH patients but not in CTEPH patients. Nevertheless, FMD did not appear to be correlated with NT-proBNP baseline levels, pulmonary vascular resistance, or the severity of PAH [177].…”
Section: Endothelial Function and Pulmonary Therapymentioning
confidence: 76%